PENGARUH PERTUMBUHAN EKONOMI, UPAH MINIMUM DAN TINGKAT PENDIDIKAN TERHADAP PENGANGGURAN DI KOTA PALOPO - Annisa Annisa; I Ketut Patra; Rahmad Solling Hamid (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to analyze the influence of several main factors, namely economic growth, minimum wages, and education levels, on the unemployment rate in Palopo City using a quantitative approach through multiple linear regression on time-series data during the period 2010-2023. Although the three variables have theoretical relevance in influencing the unemployment rate, the results of the study show that partially or simultaneously, there is no significant influence of economic growth, minimum wages, and education levels on the unemployment rate in Palopo City. Statistically, the contribution of the three variables only reaches 20.9%, while the rest, namely 79.1%, is influenced by other factors not included in this analysis model. This finding indicates a mismatch between the existing education system and the needs of the local labor market, where many graduates do not have skills that are in accordance with the developing job sectors. Therefore, this study suggests the need for more adaptive and relevant local policies, which not only focus on increasing wages and education, but also on creating better quality jobs that are in accordance with market needs, in order to reduce unemployment and improve the welfare of the Palopo City community as a whole.